AUTOMATIC PROCESS OF GENERATING TRAFFIC ANALYSIS ZONES DURING MODELING TRANSPORT SYSTEM - , Е. С. (Municipal economy of cities. Series: «Economy science», 2016)
Modelling transportation systems is an important tool of modern transportation planning. During the modelling process a number of simplifications are made by a researcher that in some cases may lead to errors in the forecasting abilities of the model. Modelling the smallest geographical unit of the model, traffic analysis zone, can be one of those errors. In this paper an algorithm for an automatic generalization of traffic analysis zones is presented. The algorithm is based on barriers and land use analysis and correct for the size of traffic zone. Current method allows to use uniform assumptions to model traffic analysis zones for different objects and to specify the minimum and maximum dimensions of the zone on the basis of research question or assumptions of the researcher. Further interest of the research is to solve the traffic assignment for the object and compare the forecasting abilities of the model depending on the number and size of the traffic zones. Keywords: modelling, transportation analysis zones, algorithm, geographic informational systems, aggregation, disaggregation.